Zakat and Waqf As an Economic Development - Deva Wijayanti; Tika Widiastuti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
The public financial sector is experiencing quite dynamic developments from time totime. Its development is also influenced by the character of the system of government that occurs at a certain time. Since the time of the Prophet (s) until now, the dynamics of the public financial sector has undergone a definite change due to the different facts faced by each time. In its development there are fixed and some are changing. This study is use literature review method, literature review is a study conducted by researchers by collecting a number of books, magazines related to problems and research purposes. Develop a sense of social responsibility in people who have excess wealth. Zakat is a mandatory provision in the economic system so that in its implementation is carried out through official or legal institutions. Waqf recipients from the community are done in an easy way, among others through mobile banking, Short Message Service and waqf kiosks. In Malaysia to develop waqf assets, investments are made through Malaysian sukuk and capital market instruments issued by the Securities Commission in February 2001.